The Influence of Influencer Credibility and Online Customer Reviews on Purchasing Decisions for Muslim Fashion Products from the Heylocal Brand with Brand Trust as a Mediator - Mahardika, Salwa Bunga; Sholahuddin, Muhammad (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of influencer credibility and online customer reviews on the purchase decision of Heylocal Muslim fashion products, with brand trust as a mediating variable. Employing a quantitative approach, data were collected through a closed-ended questionnaire based on a five-point Likert scale, distributed to consumers who had previously purchased Heylocal products and were exposed to influencer campaigns and online reviews. A purposive sampling technique was applied to select relevant respondents, and the data were analyzed using Partial Least Squares (PLS) via SmartPLS software. The results show that influencer credibility significantly affects brand trust but does not directly influence purchase decisions. In contrast, online customer reviews positively influence both brand trust and purchase decisions. Moreover, brand trust mediates the relationship between both influencer credibility and online reviews with purchase decisions. While the quantitative approach offers statistical robustness, future research may benefit from incorporating qualitative insightssuch as in-depth interviews to capture the nuanced motivations behind consumer trust and decision-making. These findings emphasize the strategic value of integrating credible influencers and customer reviews in digital marketing to foster brand trust and stimulate consumer purchases.